2017
DOI: 10.1088/1361-648x/aa63a8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Pt(5 5 3) and Rh(1 1 1) to atomic and molecular oxygen: do defects enhance subsurface oxygen formation?

Abstract: Subsurface oxygen is known to form in transition metals, and is thought to be an important aspect of their ability to catalyze chemical reactions. The formation of subsurface oxygen is not, however, equivalent across all catalytically relevant metals. As a result, it is difficult to predict the stability and ease of the formation of subsurface oxygen in metals, as well as how the absorbed oxygen affects the chemical and physical properties of the metal. In comparing how a stepped platinum surface, Pt(5 5 3), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…The PEEM observations did not provide direct evidence for the formation of subsurface oxygen, but it has been reported that on the smooth Rh(111) surface subsurface oxygen is produced at 470 K [ 31 ]. For stepped Rh surfaces, the activation energy of subsurface oxygen formation is lower than for close-packed planes such as Rh(111) [ 32 , 33 ], thus subsurface oxygen formation with an observable rate may occur at lower temperature.…”
Section: Singing In a Choir But Each Domain With Its Own Voicementioning
confidence: 99%
“…The PEEM observations did not provide direct evidence for the formation of subsurface oxygen, but it has been reported that on the smooth Rh(111) surface subsurface oxygen is produced at 470 K [ 31 ]. For stepped Rh surfaces, the activation energy of subsurface oxygen formation is lower than for close-packed planes such as Rh(111) [ 32 , 33 ], thus subsurface oxygen formation with an observable rate may occur at lower temperature.…”
Section: Singing In a Choir But Each Domain With Its Own Voicementioning
confidence: 99%
“…Subsurface adsorption of light atoms, such as hydrogen, carbon, and oxygen, has been investigated on several transition metals, including aluminum, nickel, copper, rhodium, palladium, silver, and platinum to understand their role in catalytic reactions, surface reconstruction, and surface oxidation, yet the conditions of their formation, their chemical properties, and the microscopic mechanisms of their participation in surface processes are not yet completely understood. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Lattice-gas models that include surface and subsurface sites can help to narrow the gap in fundamental knowledge by capturing the interplay between adatoms bound above and below the surface of a crystalline solid, ultimately advancing our conceptual understanding of the nature and prevalence of subsurface adsorption in surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Subsurface adsorption of light atoms, such as hydrogen, carbon, and oxygen, has been investigated on several transition metals, including aluminum, nickel, copper, rhodium, palladium, silver, and platinum to understand their role in catalytic reactions, surface reconstruction, and surface oxidation, yet the conditions of their formation, their chemical properties, and the microscopic mechanisms of their participation in surface processes are not yet completely understood. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Lattice-gas models that include surface and subsurface sites can help to narrow the gap in fundamental knowledge by capturing the interplay between adatoms bound above and below the surface of a crystalline solid, ultimately advancing our conceptual understanding of the nature and prevalence of subsurface adsorption in surface chemistry.…”
Section: Introductionmentioning
confidence: 99%